Students Academic Stress and Implications in Counseling - Abdul Halim Ade; Zikra Zikra (Universitas Negeri Padang, 2019)
Academic stress is a condition where there is a mismatch between environmental demands and the actual resources owned by students so that they are increasingly burdened by various school and academic pressures and demands. The fact that occurs in the field there are still students who experience academic stress in following the teaching and learning process in school, both viewed from the physiological, psychological, and attitude aspects. This study aims to describe the description of the academic stress level of high school students from physiological symptoms, psychological symptoms, and attitude symptoms. This type of research is quantitative research with a descriptive approach. This research was conducted at Payakumbuh 1 High School, involving 264 high school students as a research sample. Data obtained by giving research instruments in the form of a questionnaire to students. The results of the study are processed to find a percentage and then categorized according to the level of academic stress. The results of the study revealed that, firstly the academic stress of students SMA Negeri 1 Payakumbuh was in the low category with a percentage of 68.56%. This means that students SMA Negeri 1 Payakumbuh are able to control situations or conditions that cause academic-related stress. Secondly, the academic stress of students related to physiological symptoms is in the low category. Thirdly, the academic stress of high school students related to psychological symptoms is in the low category. Third, the academic stress of high school students related to attitude symptoms is in the low category.